Reply to Dews, and a plea for Schelling. Issue 1 (2nd January 2017) - Gardner, Sebastian
ABSTRACT: The discussion is a response to Dews on the question of how Schelling's Freiheitsschrift should be interpreted. It falls into two halves, the first defending my interpretation, and the second expanding on the case that Dews makes for the unavoidability of metaphysics in the theory of human freedom, with which I am in full agreement. The main criticism that Dews makes of my reading is that the argument I attribute to Schelling concerning the metaphysical significance of evil rests on Kantian assumptions regarding the existence of pure practical reason, which Schelling rejects. I argue that, though certainly matters are more complicated than my earlier discussion made them seem, Schelling remains sufficiently close to Kant for the argument I attribute to avoid inconsistency. In the second half I raise what I claim to be a neglected but important question: Why is the legacy of classical German philosophy not regarded as significant for contemporary discussion of human freedom? My answer in brief is that the concept of freedom has undergone a profound contraction. In this context I also try to define more precisely what is distinctive of Schelling's view of human freedom.